2018
DOI: 10.3390/en11113239
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Energy Saving Potential for Semi-Transparent PV Window in Southwest China

Abstract: To study Semi-Transparent photovoltaic (STPV) windows, experiments were conducted to test the energy potential of STPV window installed in buildings. Two identical rooms were built up as experimental units; one was fitted with amorphous silicon (a-silicon) photovoltaic (PV) windows, and another was fitted with a conventional window. The interactional influence was analyzed among air conditioning energy consumption, lighting energy consumption, and energy generation. It can be concluded that STPV windows could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Moreover, Figure 7 shows that heat gain cut down by almost 65% throughout all the five orientations, which is related to that transmittance of glass is much higher than that of BIPV modules [36]. Tian et al [37] examined the energy potential of semi-transparent photovoltaic windows in terms of energy output, the energy consumption of lighting and energy consumption of air conditioning. The result showed that semi-transparent photovoltaic windows able to save nearly 30% of the total building load on a standard sunny day.…”
Section: Building Integrated Photovoltaics and Climate Effect 231 Heating And Cooling Performance Of Building Integrated Photovoltaicsmentioning
confidence: 99%
“…Moreover, Figure 7 shows that heat gain cut down by almost 65% throughout all the five orientations, which is related to that transmittance of glass is much higher than that of BIPV modules [36]. Tian et al [37] examined the energy potential of semi-transparent photovoltaic windows in terms of energy output, the energy consumption of lighting and energy consumption of air conditioning. The result showed that semi-transparent photovoltaic windows able to save nearly 30% of the total building load on a standard sunny day.…”
Section: Building Integrated Photovoltaics and Climate Effect 231 Heating And Cooling Performance Of Building Integrated Photovoltaicsmentioning
confidence: 99%
“…The study reported annual energy saving of 322.9 kWh with a panel efficiency of 13%, payback period of 13.8 yrs. Similarly, Tian et al [46] analyzed the energy saving potential of semi-transparent PV (STPV) window made of amorphous silicon (a-silicon) at four sites in Southwest China. The energy generated at these sites was reported to be 402.1, 314.1, 233.55, and 216.5 kWh at Lhasa, Kunming, Chengdu, Guiyang sites, respectively.…”
Section: Asian Regionmentioning
confidence: 99%
“…Indeed, about 80% of the BIPV's installations are roof-mounted and the remaining ones 20% are mounted on the facade in which they act as a rain screen (Hestnes, 1999). Due to the recent advancements in terms of solar energy technology, BIPV cannot only be perfectly integrated into buildings, but also can provide more aesthetic architectural expression, such as coherent variations in proportions, surfaces, models, colors, and textures (Tian et al, 2018). Also, BIPV can be composed of semi-transparent PV panels that can be successfully integrated into architectural glazing.…”
Section: Background and Motivationmentioning
confidence: 99%